2012
DOI: 10.1111/1751-7915.12018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of population dynamics of Corynebacterium glutamicum by multiparameter flow cytometry

Abstract: SummaryPhenotypic variation of microbial populations is a well-known phenomenon and may have significant impact on the success of industrial bioprocesses. Flow cytometry (FC) and the large repertoire of fluorescent dyes bring the high-throughput analysis of multiple parameters in single bacterial cells into reach. In this study, we evaluated a set of different fluorescent dyes for suitability in FC single cell analysis of the biotechnological platform organism Corynebacterium glutamicum. Already simple scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…4) showing a high MP in all samples. It has been implied previously for that MP decreases in a cell population during the stationary phase (Neumeyer et al, 2013), but glucose availability was not clearly identified as source for the MP shift. 4A).…”
Section: Impact Of Compartment Specific Glucose Availability On Cell mentioning
confidence: 79%
See 2 more Smart Citations
“…4) showing a high MP in all samples. It has been implied previously for that MP decreases in a cell population during the stationary phase (Neumeyer et al, 2013), but glucose availability was not clearly identified as source for the MP shift. 4A).…”
Section: Impact Of Compartment Specific Glucose Availability On Cell mentioning
confidence: 79%
“…The DiOC 2 (3) staining was performed as previously described (Neumeyer et al, 2013). The DiOC 2 (3) staining was performed as previously described (Neumeyer et al, 2013).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the use of fluorescence proteins, the use of the fluorescing dyes Syto 9, propidium iodide, and 3,3=-diethyloxacarbocyanine iodide [DiOC2(3)] proved to be useful for the identification of subpopulations with reduced viability and membrane potential within C. glutamicum populations (84). Other studies employed in situ reverse transcription-PCRs at a single-cell level in combination with a single-cell beta-galactosidase assay to monitor heterogeneous expression of the lac operon in Salmonella enterica serovar Typhimurium (85).…”
Section: Measuring Phenotypic Heterogeneity At a Single-cell Levelmentioning
confidence: 99%
“…Recent studies using multiparameter flow cytometry revealed phenotypic heterogeneity in terms of viability, membrane potential and growth activity of C. glutamicum wild type cells grown in shake flasks [17]. However, population heterogeneity during production processes has not been studied in detail for this species, yet.…”
Section: Introductionmentioning
confidence: 99%